ELASTO-PLASTIC FINITE ELEMENT ANALYSIS OF METAL-MATRIX COMPOSITE PLATES WITH HOLE UNDER PLANE LOADING - Okumu, Fuat; Turgut, Aydin; Sancaktar, Erol (American Society of Mechanical Engineers (ASME), 1999)
The elasto-plastic stress analysis of composite plates with hole has been carried out by the finite element method. For this purpose, an isoparametric rectangular element with nine nodes has been chosen and the lagrange polynomial has been used as interpolation function. Steel-aluminum composite has been manufactured by using mould under the action of 30 MPa pressure and heating up to 600°C. Mechanical properties and yield strength of the composite material have been obtained experimentally by using a strain gauge in the tensile testing machine. The composite plates in various dimensions have been. obtained by changing the diameter of the hole. The various tension loads which are increased step by step from beginning of the yield have been applied to these plates. The expansions of plastic regions have been illustrated for various cases. According to orientation angle and applied loads, elastic, plastic and residual stresses have been obtained. © 1999 American Society of Mechanical Engineers (ASME). All rights reserved.
ASME 1999 International Mechanical Engineering Congress and Exposition, IMECE 1999 -- 14 November 1999 through 19 November 1999 -- Nashville -- 176006
Keywords: Elastoplasticity; Fatigue testing; Finite element method; Materials testing apparatus; Metal testing; Polymer matrix composites; Pressure vessels; Strain; Strain gages; Stress analysis; Tensile testing; Aluminum composites; C: Mechanical properties; Composite plates; Elasto-plastic finite element analysis; Elasto-plastic stress; Heating up; Interpolation function; Iso-parametric; Lagrange's polynomials; Stresses analysis; Metallic matrix composites